Karakteristik ikan bulan-bulan (Megalops cyprinoides) dan potensinya sebagai tepung ikan - Reni Tri Cahyani; Stephanie Bija; Leny Tang Nga Sugi (Program Studi Ilmu dan Teknologi Pangan, Universitas Yudharta, Pasuruan, 2020)
Fish is very good for health because it contains various important nutrients such as protein, fat, and minerals. Fish flour can be added to food product to obtain physiological effects and improve the nutritional status of fortified foods. This study aims to examine the characteristics of Bulan - bulan fish (Megalops cyprinoides ) and its potential as fish flour. This research was divided into two stages, namely characterization of the fresh fish and preliminary analysis of its potentia l as fish flour. The data obtained were analyzed descriptively. The results showed that the edible portion of fresh fish was only 42.81%, whereas the remaining of 57.19% was processing waste. The fish had a high protein content of 21.43%, fat content was 1 3.32%, ash content was 12.80%, moisture content was 42.29% and carbohydrate content was 10.19%. The fish flour had powdered form; clean, normal, and bright appearance; bright brownish yellow color; quite dry and non - lumpy texture; and specific aroma. The y ield of the fish flour was 22,75%, whereas t he p r otein content of the fish flour was 55.44% wh ich comply with the protein’s requirement of quality II fish flour.